A SYSTEMATIC LITERATURE REVIEW LITERASI MATEMATIKA: TINJAUAN PENELITIAN ANTARA 2019-2023 : SYSTEMATIC LITERATURE REVIEW LITERASI MATEMATIKA: TINJAUAN PENELITIAN ANTARA 2019-2023 - Priscilia, Priscilia Monica Praneswari; Wijayanti, Kristina; Rachmani Dewi, Nuriana; Junaedi , Iwan; Noriza Munahefi, Detalia; Mariani, Scolastika; Rosyida, Isnaini (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2024)
Mathematical literacy plays an important role in the success of mathematics learning. Mathematical literacy is closely related to several mathematical abilities such as mathematical reasoning and problem solving. Therefore, mathematical literacy is an important focus in mathematics learning. This study aims to analyze and identify trends in the novelty of research on mathematical literacy in the last 5 years. This research was conducted with a systematic literature review. The data sources for this study are from Google Scholar and Scopus. The tool used in data collection is Publish or Perish software with the keyword mathematical literacy with a publication range from 2019 to 2023. The data analysis uses the help of the Covidence website, Microsoft Excel, and Vos Viewer. The research found in the data collection process was 400 articles which were then analyzed by adjusting the inclusion and exclusion categories, title, abstract and article content using the help of the Covidence website. The results obtained from the data analysis were 13 studies indexed by Scopus and 13 other studies accredited by Sinta. The results of this study indicate that the trend of new mathematical literacy research is related to augmented reality, guided inquiry learning, and mathematical self-efficacy.